Use some statistical algorithms in mock hacking satellite image - الراوي, اسماء غالب; عبدالودود, محمد (Journal of Economics and Administrative Sciences, 2025)
In the recent years, remote sensing applications have a great interest because it's offers many advantages, benefits and possibilities for the applications that using this concept, satellite it's one must important applications for remote sensing, it's provide us with multispectral images allow as study many problems like changing in ecological cover or biodiversity for earth surfers, and illustrated biological diversity of the studied areas by the presentation of the different areas of the scene taken depending on the length of the characteristic wave, Thresholding it's a common used operation for image segmentation, it's seek to extract a monochrome image from gray image by segment this image to two region (foreground & background) depending on pixels intensity to reducing image distortion, and also separated the target area from the rest of scene features under study, so we seek to used number of  thresholding techniques in this paper for clarify the importance of this concept in image processing and we proposed a new statistical thresholding techniques which compared with techniques used, and the result showed the advantage of proposed techniques that achieved from applying the techniques on multispectral satellite image takin for an area west of Iraq that characterized their environmental diversity so it's a good case to study.